Consider the Lie group $GL(n, \mathbb{R})$. Since $GL(n, \mathbb{R})$ is an open subset of the space $M_{n,n}(\mathbb{R})$ of $n \times n$ matrices, we can identify the tangent space (Lie algebra) $T_{e}GL(n, \mathbb{R})$ with $M_{n,n}(\mathbb{R})$, where $e$ is the identity matrix. I'm trying to understand the following:

For all $x, y \in M_{n,n}(\mathbb{R}) = T_{Id}GL(n, \mathbb{R})$ we have $[x, y] = xy -yx$ where $[\cdot, \cdot]$ is the Lie algebra bracket.

According to the question Is the Lie bracket of a Lie Algebra of a Matrix Lie Group always the commutator?, this seems to be the case for matrix Lie groups in general.

So far, I've worked out the following: Let $x \in M_{n,n}(\mathbb{R}) = T_{Id}GL(n, \mathbb{R})$ and let $X \in \Gamma^{inv}(TG)$ be the left invariant vector field corresponding to $x$, i.e. with $X(e) = x$. By openness, we can choose $\epsilon > 0$ such that the curve $(-\epsilon, \epsilon) \ni t \mapsto e + tx$ through the identity is contained in $GL(n, \mathbb{R})$. For $g \in GL(n, \mathbb{R})$ let $L_g$ be the left multiplication by $g$ in $GL(n, \mathbb{R})$. Using left invariance of $X$ calculate: $$X(g) = ((L_g)_{*}X)(g) = D_eL_g(X(e)) = D_eL_g(x) = \frac{d}{dt}|_{t=0}g(e+tx) = gx$$ Now, the above implies for $f \in C^{\infty}(GL(n, \mathbb{R}))$ and $g \in GL(n, \mathbb{R})$: $$X(g)(f) = (D_gf)(gx)$$ where we identify the tangent vector $X(g)$ with the corresponding derivation at $g$.

Now how do I calculate $[x,y] \stackrel{def.}{=} [X, Y](e) \stackrel{\text{WHY?}}{=}xy-yx$ from this?

  • 1
    $\begingroup$ I presume you're working with the definition $[X,Y]_p(f) = X_p(Yf)-Y_p(Xf)$? Or do you want the Lie derivative $\mathscr L_XY$? For the latter, you'll need to actually show that the $X$-flow is given by $\phi_t(g) =ge^{tx}$. $\endgroup$ Aug 6 '16 at 16:19
  • $\begingroup$ Yes, I'm working with the definition you're mentioning. I haven't learned about Lie derivative. $\endgroup$ Aug 7 '16 at 9:12
  • $\begingroup$ @AlexM. Would you be able to elaborate on your comment? I don't seem to recognize the statement you're referring to in this form. If it is completely standard as you say, could you either give a reference for it or a quick proof with relation to my question? $\endgroup$ Aug 9 '16 at 10:02
  • 1
    $\begingroup$ @TomBombadil: I no longer have the time to write the proof myself, but a web search for "Lie bracket matrix group" returns plenty if results, including this one that you may find useful (see results 3.1 - 3.7) $\endgroup$
    – Alex M.
    Aug 13 '16 at 8:00

Perhaps this won't satisfy you, but we know that $ad:\mathfrak{g}\to\mathfrak{gl}(\mathfrak{g})$ and $Ad:G\to GL(\mathfrak{g})$ satisfy $d(Ad)_e=ad$, for any Lie group. Here, since we are working with matrices in $\mathbb{R}^{n^2}$, this implies:

If $X,Y\in\mathfrak{gl}_n$, and $g(t)$ is a path of matrices in $GL_n$ such that $g(0)=I_n$ and $g'(0)=X$, then: $$ ad(X)(Y)=\frac{d}{dt}Ad(g(t))(Y)\bigg|_{t=0}=\frac{d}{dt}g(t)Yg(t)^{-1}\bigg|_{t=0}=XY-YX $$ with the last line being by the product rule.

EDIT: Here's a more hands-on approach, following some notes by Wolfgang Ziller (I always get confused during these calculations! I hope this helps someone.)

Let $X,Y\in T_eG$ be tangent vectors at the identity ($G=GL_n(\mathbb{R}))$. Then since $G$ is an open submanifold of $Mat_n(\mathbb{R})$, we can make a canonical identification of all its tangent spaces with $Mat_n(\mathbb{R})$. Once we do this, if $g\in GL_n(\mathbb{R})$ then $(dL_g)_e(X)=gX$, (since matrix multiplication is linear) so the left invariant vector field associated to $X$ is $gX$ at the point $g\in G$. Similarly the one associated to $Y$ is $gY$ at $g$.

Next, notice that if $y_{ij}$ is the coordinate function on matrices picking out the $(i,j)$th entry in the tangent space $T_{h}G$, then $(gX)(y_{ij})=dy_{ij}(gX)=(gX)_{ij}$ because $y_{ij}$ is a linear function. Note that $(gX)_{ij}$ should be thought of as the function defined in a small neighborhood of $h$ given by $g\mapsto (gX)_{ij}$.

Now we can compute the value of the bracket of $X$ and $Y$ at the identity $e$:

$$ [X,Y](y_{ij})=X(Y(y_{ij}))-Y(X_{ij}))=X(g\mapsto(gY)_{ij})-Y(g\mapsto(gX)_{ij}) $$ Now $d(g\mapsto (gY)_{ij})=\sum\limits_{k=1}^ny_{kj}dy_{ik}$, so $$ X(g\mapsto(gY)_{ij})=\sum\limits_{k=1}^ny_{kj}dy_{ik}(X)=\sum\limits_{k}x_{ik}y_{kj}=(XY)_{ij} $$ Similary, $Y(g\mapsto(gX)_{ij})=(YX)_{ij}$, so $[X,Y](y_{ij})=(XY-YX)_{ij}$. This says that the entries of $[X,Y]$ are the same as the entries of $(XY-YX)$, so we're done.

  • $\begingroup$ Hi, I'm wondering why is $d(g\mapsto (gY)_{ij})=\sum_{k=1}^ny_{kj}dy_{ik}$ (I'm also looking at the notes). I'm thinking in this step we are just differentiating the coordinate functions. Am I correct? But in this case, do we differentiate it $n^2$ times (since it's $n^2$-dim?) or $n$ times? But if differentiate $n^2$ times, I also got stuck in the calculations... Thanks! $\endgroup$
    – chikurin
    Jan 28 '19 at 3:02

I've now been able to do the calculation myself with a bit of inspiration from freeRmodule's answer:

Using the calculations presented in the question, we calculate the adjoint operator for the Lie group $G := GL(n, \mathbb{R})$. For $g \in G$ and $x \in M_{n,n}(\mathbb{R})=T_{Id}G$ with corresponding left invariant vector field $X$ we have: $$Ad(g)(x) = ((R_{g^{-1}})_{*}X)(Id) = D_gR_{g^{-1}}(\overbrace{X(g)}^{=gx}) = gxg^{-1}$$

By a statement which holds for Lie groups in general we then calculate the Lie bracket of $x$ and $y$ (noting that the Lie group exponential $exp_G$ on $G$ is simply the matrix exponential $Exp$): \begin{align*} [x,y] &= \frac{d}{dt}|_{t=0} Ad(exp_G(tx))(y) = \frac{d}{dt}|_{t=0}Exp(tx)yExp(-tx) \\ &= \left( \frac{d}{dt}|_{t=0}Exp(tx) \right)\cdot y \cdot Id + Id \cdot y \cdot \left( \frac{d}{dt}|_{t=0}Exp(-tx) \right) \\ &= xy -yx \end{align*}


I think the sensible way to get an intuition for this is to just look at the Taylor expansion of the group commutator:

$$e^{\varepsilon x} e^{\varepsilon y} e^{-\varepsilon x} e^{-\varepsilon y}$$

Which to second order is $1+\varepsilon^2(xy-yx)$. Presumably you know how to prove that the second derivative of the above expression is equivalent to the derivative-of-the-adjoint definition.


I know how to do this for linear algebraic groups over an algebraically closed field $k$. I assume it works the same for Lie groups? I don't know Lie groups. Anyway, I hope this is helpful to you.

Let $G = \textrm{GL}_n$, let $R = k[T_{ij} : 1 \leq i, j \leq n]$, and let $A$ be the localization of $R$ at the function $\textrm{Det}$. Then $A = k[G]$ is the coordinate ring of $G$.

By definition, the tangent space of $G$ at $1_G$ is the $k$-vector space of derivations $\textrm{Der}_k(A,k)$ of $A$ into $k$, i.e. those $k$-linear maps $\delta: A \rightarrow k$ for which $\delta(fg) = f(1_G)\delta(g) + g(1_G) \delta(f)$ for all $f, g \in A$.

Every $\delta \in \textrm{Der}_k(R,k)$ extends uniquely, using the quotient rule, to an element of $\textrm{Der}_k(A,k)$. And $\textrm{Der}_k(R,k)$ is isomorphic as $k$-vector spaces to $M_n(k)$, the space of $n$ by $n$ matrices: every $\delta \in \textrm{Der}_k(R,k)$ is completely determined by its values on the coordinate functions $T_{ij}$, so associate $\delta$ to the matrix $(\delta(T_{ij})) \in M_n(k)$.

Now, let $L(G)$ be the subspace of $\textrm{Der}_k(A,A)$ (derivations from $A$ to itself) consisting of those $D$ which are left invariant: this means that $\lambda_x \circ D = D \circ \lambda_x$ for all $x \in G$. Here if $x \in G$, $\lambda_x$ is the $k$-algebra isomorphism $A \rightarrow A$ given by $\lambda_x(f)(y) = f(x^{-1}y)$ for all $y \in G$.

One can show that $\textrm{Der}_k(A,k)$ is isomorphic as $k$-vector spaces of $L(G)$: if $D \in L(G)$, we associate the element $\delta \in \textrm{Der}_k(A,k)$ given by $\delta(f) = D(f)(1_G)$. The inverse map is more complicated to describe: if $\delta \in \textrm{Der}_k(A,k)$, then we associate the element $D \in L(G)$ which sends an $f \in A$ to the element of $A$ given by the formula $x \mapsto \delta(\lambda_{x^{-1}}(f))$.

Now, $L(G)$ is naturally a Lie algebra with the bracket operation $[D,D'] = D \circ D' - D' \circ D$. Using the $k$-vector space isomorphism $L(G) \rightarrow \textrm{Der}_k(A,k)$, we transfer the bracket operation to $\textrm{Der}_k(A,k)$ to give $\textrm{Der}_k(A,k)$ the structure of a Lie algebra. The vector space $\textrm{Der}_k(A,k)$, considered as a Lie algebra, is called the Lie algebra of $G$ and is often denoted $\mathfrak g$.

Now you identify the Lie algebra of $G$ with $M_n(k)$, and you want to describe the bracket operation on $M_n(k)$ explicitly. So you need to transfer the bracket operation on $L(G)$ using the isomorphisms

$$M_n(k) \rightarrow \textrm{Der}_k(R,k) \rightarrow \textrm{Der}_k(A,k) \rightarrow L(G)$$

If you go through these isomorphisms, you will see that an element $D \in L(G)$, identified as an element of $M_n(k)$, is the $n$ by $n$ matrix whose $ij$th entry is $D(T_{ij})(1_G)$. Conversely, if you begin with an $n$ by $n$ matrix $A = (a_{ij})$, the corresponding element $D$ in $L(G)$ is given by the formula

$$D(T_{ij}) = \sum\limits_l T_{il}a_{lj}$$

Now, let $A, B \in M_n(k)$, and let $D,D'$ be the corresponding elements of $L(G)$. To show that the Lie bracket transfers over the way you want, it is enough to show that $D \circ D'$ is the element of $L(G)$ which corresponds to the product $AB$.

Let $C$ be the matrix corresponding to $D \circ D'$. The $ij$th entry of $C$ is $(D \circ D')(T_{ij})(1_G)$.

Now $D'(T_{ij}) = \sum\limits_l T_{il}b_{lj}$, and $D(T_{il}) = \sum\limits_s T_{is}a_{sl}$. Hence

$$D \circ D'(T_{ij}) = \sum\limits_{l,s} T_{is}a_{sl}b_{lj}$$ and so $c_{ij}$ is the evaluation of this polynomial at the identity matrix $1_G$. Now $T_{is}(1_G) = \delta_{is}$, and so

$$c_{ij} = \sum\limits_l a_{il}b_{lj}$$ done.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.